I survived the Wellington Avalanche, 1910 - Tarshis, Lauren; Dawson, Scott (New York, NY : Scholastic Paperbacks, 2022)
"The snow is coming down faster than train crews can clear the tracks. In a tiny town in the Cascade Mountains, Janie Pryor-and the other passengers trapped on the Seattle Express train-wait for the horrific blizzard to end. One day passes, then two, three...six days. Secretly, Janie doesn't mind being stuck on the mountain. She's safe from the brutal gangster chasing after her. And so far, nobody on the train knows about the stolen jewels Janie has with her. But then the mountain breaks apart and Janie is caught in a ferocious wave of snow and giant rocks. Can she make it out alive?"
Includes bibliographical references.
570L
Decoding demand: 87 (very high) Semantic demand: 99 (very high) Syntactic demand: 81 (very high) Structure demand: 88 (very high)
Keywords: Avalanches -- Juvenile fiction; Railroad trains -- Juvenile fiction; Washington (State) -- Juvenile fiction; Cascade Range -- Juvenile fiction; Wellington (Wash.) -- History -- 20th century -- Juvenile fiction; Historical fiction; Action and adventure fiction